(untitled) (Global Journal of Sciences, 2024)
The aim of this manuscript is to introduce a novel form of H-H inequality via ψ-RLFIO for preinvex functions. By employing this approach, we construct a new lemma. In addition, based on this newly derived fractional identity, some new estimation of fractional H-H inequality involving m-preinvex via ψ-RLFIO is investigated. Further, we add some mean-type applications.